2008
DOI: 10.1103/physrevlett.101.120503
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Parallelism as a Tool for Ensemble Spin Dynamics Calculations

Abstract: Efficient simulations of quantum evolutions of spin-1/2 systems are relevant for ensemble quantum computation as well as in typical NMR experiments. We propose an efficient method to calculate the dynamics of an observable provided that the initial excitation is "local". It resorts a single entangled pure initial state built as a superposition, with random phases, of the pure elements that compose the mixture. This ensures self-averaging of any observable, drastically reducing the calculation time. The procedu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
58
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 32 publications
0
58
0
Order By: Relevance
“…It has been shown that a state corresponding to a random superposition of Ising states manifests thermal features. Specifically, the results for local observables led to the same outcomes obtained with a mixed state at infinite temperature [35,53,54]. The state is constructed so that the probability amplitudes of the basis vectors have all the same absolute value, 1/ √ D, but differ by a random phase e i2πϕ , where ϕ is a uniformly distributed random variable in [0, 1).…”
Section: A Delocalization Of the Initial State And Thermal Propertiesmentioning
confidence: 99%
“…It has been shown that a state corresponding to a random superposition of Ising states manifests thermal features. Specifically, the results for local observables led to the same outcomes obtained with a mixed state at infinite temperature [35,53,54]. The state is constructed so that the probability amplitudes of the basis vectors have all the same absolute value, 1/ √ D, but differ by a random phase e i2πϕ , where ϕ is a uniformly distributed random variable in [0, 1).…”
Section: A Delocalization Of the Initial State And Thermal Propertiesmentioning
confidence: 99%
“…The recent progress on the experimental control of cold atoms [5,7,15], trapped ions [16], Ryderberg atoms [17], polar molecules [18,19] and nitrogen-vacancy centers in diamond [20] in solid state systems leads to promising which we observe and control the All experiments are performed on a NMR spectrometer whose superco a strong magnetic field of 7 Tesla spins have the same resonance fr MHz and are subject to mutual di composing a 3D spin-coupling ne dipolar interaction scales with 1/ onance width of 7.9 kHz of the N the homogeneous broadening (Se of the sample). The system is lef temperature and the thermal equ ing density operator for the spins in the high-temperature limit as considering that the Zeeman inter than the dipolar one (ω z = 300 M Experimental method and quan spin-spin interaction Hamiltonian Zeeman rotating frame is tonian (ω z d ij ), since the effects of the non-sec terms are negligible [29].…”
Section: System and Experimental Setupmentioning
confidence: 99%
“…However, experimentally addressing 3D manybody systems in a controlled manner poses severe experimental problems (5,8,14,16). Non-equilibrium dynamics of many-body systems has been investigated to provide complementary information about a large variety of situations but also remains challenging (18)(19)(20)(21)(22)(23)(24)(25)(26). Therefore, finding different experimental situations, new approaches and techniques for controlling and observing many-body dynamics can lead to new approaches for studying manybody physics.…”
mentioning
confidence: 99%
“…The control of interaction anisotropy, e.g., the switch from a dipolar to an XY (planar) interaction, provides a tool for enhancing the transfer of quantum information [11,12]. In particular, the interactions can be sequentially turned on and off to prune some branches in real space so that an excitation is directed to a desired target through a specific pathway [13].…”
Section: Introductionmentioning
confidence: 99%